2019
DOI: 10.21475/ajcs.19.13.11.p2015
|View full text |Cite
|
Sign up to set email alerts
|

Salt-induced changes in solutes, pigments and essential oil of two basil (Ocimum basilicum L.) genotypes under hydroponic cultivation

Abstract: The aim of this study was to evaluate the effect of salt stress on the contents of inorganic and organic solutes, pigments and essential oil in two basil genotypes cultivated in hydroponic system. The experiment was carried out in a greenhouse. Treatments were distributed in randomized blocks, in a 2 × 2 factorial arrangement, corresponding to two contrasting genotypes (‘Toscano folha de alface’ (TFA) and ‘Gennaro de menta’ (GM)) and two salt levels (0 - control and 80 mM NaCl), with six replicates. The Na+, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…An increase was evident during the last days, resulting in similar K levels in all treatments at the final harvest. This increase may be due to the role of K in osmoregulation, since it is considered, along with Cl, among the inorganic solutes with a greater contribution to the osmotic adjustment in basil [21]. Similar regulatory involvement in osmotic stress may be ascribed to Ca, the accumulation of which was induced by the two higher salinity levels at the early phase of stress.…”
Section: Exploration Of Salinity-tolerance Thresholds Of Basilmentioning
confidence: 96%
See 2 more Smart Citations
“…An increase was evident during the last days, resulting in similar K levels in all treatments at the final harvest. This increase may be due to the role of K in osmoregulation, since it is considered, along with Cl, among the inorganic solutes with a greater contribution to the osmotic adjustment in basil [21]. Similar regulatory involvement in osmotic stress may be ascribed to Ca, the accumulation of which was induced by the two higher salinity levels at the early phase of stress.…”
Section: Exploration Of Salinity-tolerance Thresholds Of Basilmentioning
confidence: 96%
“…An accumulation of free amino acids has been usually reported in various plants exposed to abiotic stress [32,33]. Neto et al (2019) [21] measured the total content of amino acids of two basil varieties grown under 80 mM NaCl and reported a marginal increase in both leaves and roots. There is a tight relationship between amino acid metabolism and plant response to stress, due to the multiple roles of certain amino acids in stress mitigation; i.e., osmoprotectants, ROS scavengers, N source and storage, and as alternative substrates for mitochondrial respiration [32][33][34].…”
Section: Exploration Of Salinity-tolerance Thresholds Of Basilmentioning
confidence: 99%
See 1 more Smart Citation
“…Muitas pesquisas têm demostrado que as plantas aromáticas, como o manjericão (O. basilicum L.), podem tolerar salinidade moderada se apresentando assim como uma cultura alternativa em solos degradados por sal sem perda relevante de rendimento (Bione et al, 2014;Maia et al, 2017;Reyes-Pérez et al, 2021). Por sua grande variedade de utilizações e propriedades antimicrobianas e medicinais é uma cultura de alto valor comercia (Barbieri et al, 2012;Santos et al, 2012;Neto et al, 2019;Scagel et al, 2019). Research, Society andDevelopment, v. 11, n. 8, e49011831298, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i8.31298 Nesse sentido Bione et al (2014) avaliaram os efeitos de águas salobras em quatro níveis de salinidade diferentes (1,45; 3,80; 6,08 e 8,48 dS m -1 ) sobre o crescimento e à produção de plantas de manjericão em sistema hidropônico NFT.…”
Section: Simões Et Al (unclassified
“…Walters and Currey (2015) and Santos et al (2019) found no significant differences for growth variables and production of basil under cultivation in the hydroponic systems NFT and DFT. The use of marginal quality water, such as brackish water, increased the yield of essential oil in the basil genotypes 'Grecco a Palla' (Gondim Filho et al, 2018) and 'Gennaro de Menta' (Azevedo Neto et al, 2019;Silva et al, 2019). In addition, the use of treated domestic effluents proved to be viable for the cultivation of this crop Gonçalves et al, 2019) in DFT hydroponic system in tubes.…”
mentioning
confidence: 99%